PENINGKATAN IMPLUSE BUYING PADA WANITA BEKERJA DI JAWA TENGAH - Rahmi Yuliana; Himawan Arif Sutanto (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
Knowledge about consumers is the key to planning a marketing strategy in the company, the customer can be the most valuable asset so the company needs to maintain and create equity. The development of technology is very rapid from the development of new product markets to meet the increasing needs of society as well. business people lead to the establishment of many shopping facilities that offer services and facilities that make it easier, then this can attract consumers. Impulsive buying and unplanned buying by some researchers are not differentiated. Semuel, (2005) does not distinguish between unplanned buying and impulsive buying but gives important attention to researchers, customers must focus on the interaction between point of sale with buyers who are often ignored. Personal selling is a form of individual communication where a salesperson deals directly with potential buyers and tries to influence them to buy their products or services. Hedonic shopping according to Semuel (2005) reflects an instrument that directly presents the benefits of experience in spending, such as pleasure, new things. Multiple Linear Regression Analysis is used to analyze the effect of several independent or independent variables (X) on one dependent or dependent variable (Y) together.